LAW IMPLEMENTATION OF PERSONS OF HOUSEHOLD VIOLENCE AGAINST WOMEN IN REVIEW FROM LAW NUMBER 23 OF 2004: PENERAPAN HUKUM TERHADAP PELAKU KEKERASAN DALAM RUMAH TANGGA TERHADAP PEREMPUAN DI TINJAU DARI UNDANG-UNDANG NOMOR 23 TAHUN 2004 - Hulu, Wandrinus (LPPM UPMI, 2023)
Violence that occurs in the household is a specific or special thing. The specificity lies in the relationship between the perpetrator and the victim, namely the relationship within the family and work relationship. The forms of domestic violence are: physical violence, psychological violence, sexual violence, economic violence. There was no correlation between the factors of occurrence of domestic violence between economic problems, number of children, extramarital affairs, axcessive jealousy and excessive emotions. The aim of this research is to find out legal protection efforts for women as victims of domestic violence in Medan city. The research method in this paper is normative with a statutory and conceptual approach. Meanwhile, the specification of this research is analytical descriptive. The data used secoundary data from primary legal materials in the from of laws and regulations such as Law Number 23 of 2004 conecerning the Elimination of Domestic violence (UU PKDRT). But in reality tharee victims are still complicated by all the existingregulations. So that there are still many criminal acts of domestic violence.